Combined analysis of 16S rRNA sequencing and metabolomics reveals the growth-promoting mechanism of compound probiotics in zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Zhiting Zuo; Guangting Xie; Yiman Chen; Xiaoli Yin; Baoyue Lu; Zhide Yu; Chong Han; Hu Shu (Aquaculture Reports)
Probiotics are important natural nutritional immune enhancers in aquaculture. The objective of this experiment was to investigate the effects of single or combined supplementation with marine fish probiotics on growth performance, intestinal physiology, gut microbes, and gut metabolites in zig-zag eel (Mastacembelus armatus). A total of 1500 three-month-old healthy M. armatus were randomly divided into 5 groups: CON (control group), BC (Bacillus cereus G1–11 group), EA (Exiguobacterium acetylicum G1–33 group), MIX (the compound probiotics group), PC (the commercial probiotics group), and the feeding period was 8 weeks. Growth index and growth-related gene expression were measured to reflect the growth performance of M. armatus. The results showed that the groups supplemented with probiotics promoted the growth of M. armatus, and the MIX had the most significant promotion effect (P < 0.05). The intestinal physiology was reflected by intestinal histology, intestinal digestive enzyme, and antioxidant enzyme activity (P < 0.05). 16S rRNA sequencing was used to analyze the gut microbiota of different groups. The MIX probiotics can promote the activities of intestinal digestive enzymes and antioxidant enzymes by promoting the bacteria Brevundimonas, Bacillus, and Rhodococcus in the intestine. Non-targeted metabolomics was used to analyze intestinal metabolites in each group. The compound probiotics can increase metabolites such as piperazine, phenols, glycerophospholipids, and unsaturated fatty acids. The compound probiotics can increase the number of beneficial intestinal bacteria and beneficial metabolites, promoting intestinal digestion and absorption, maintaining intestinal microbial environment homeostasis, and improving the growth of M. armatus. Overall, this study first provides a comprehensive analysis of the interactions among gut enzyme activity, microbiota, and metabolites in relation to the growth of M. armatus, while also recommending B. cereus G1–11 and E. acetylicum G1–33 for application in freshwater aquaculture.